Evaluation of heavy metal contamination level of soil at UiTM Cawangan Pahang / Syaridatul Khairiah Zulkifli - Zulkifli, Syaridatul Khairiah (2024)
The concentration of four heavy metals, such as Cu, Fe, Pb, and Zn, was studied in the soils near the female’s hostel (Kolej Tok Gajah). The aim of the study is to investigate the concentration of the selected metals in soils near the female’s hostel (Kolej Tok Gajah) and to estimate the health risk of metal exposure. The soil samples were collected from six points of a roadside near the female’s hostel, with a distance of approximately 200 m from each point, where the surface soil samples were collected (0-10 cm) using a hoe and stainless-steel scoop. The digestion mixture was filtered using Whatman 42 filter paper. Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) was used in order to determine the concentration of Cu, Fe, Pb, and Zn. Overall concentrations of Cu, Fe, Pb, and Zn in the soil samples ranged from 0-100 mg/kg, 1-892.7 mg/kg, 0.3333 mg/kg, and 0-140 mg/kg. The concentration of heavy metals in the soil showed the following decreasing trend: Fe > Zn > Cu > Pb. The potential non-cancer health risk for all metal exposure showed values below 1, which indicate no adverse effects exist. Fe has the highest value during the dry condition (1.93 x 102), while Cu has the lowest value during the wet condition (8.89 x 10-5). However, for cancer risk assessment, all of the values are greater than 1, which shows that cancer risk might occur.